Impact of herpes simplex virus detection in respiratory specimens of patients with suspected viral pneumonia - Scheithauer, S. (Infection, 2010)
BACKGROUND: Respiratory infection and failure is a commonly encountered problem in intensive care unit (ICU) patients. However, despite the accumulating body of evidence to suggest that herpes simplex virus type 1 (HSV-1) is associated with pneumonia, the exact role played by this virus in this process is still not fully understood. Therefore, to identify patients at risk, we have conducted a case–control study to characterize patients with HSV-1-positive pneumonia. PATIENTS AND METHODS: Between 2007 and 2009, all patients with suspected viral pneumonia were tested for the presence of herpes viruses using a PCR assay approach with respiratory specimens. To identify possible associations, risk factors, and impact of HSV, HSV-1-positive ICU patients (n = 51) were compared to age-, gender-, and department- and season-matched HSV-negative patients (n = 52). RESULTS: HSV-positive patients differed significantly from the HSV-negative ones only in terms of time of mechanical ventilation (13 vs. 6 days, respectively; p = 0.002). Subgroup analysis in the patients aged >60 years and in those without bacterial detection revealed a similar trend (p = 0.01 and p = 0.004, respectively). Mortality did not differ between the groups or between the HSV-1-positive patients treated with aciclovir and those who were not. A viral load >10E+05 geq/ml was associated with mechanical ventilation (20/21 vs. 17/29; p = 0.004), acute respiratory distress syndrome (ARDS; 19/21 vs. 18/29; p = 0.005), sepsis (18/21 vs. 14/29; p = 0.008), detection of a bacterial pathogen in the same specimen (10/21 vs. 4/29; p = 0.01) and longer ICU stay (25 vs. 30 days; p = 0.04). CONCLUSION: Despite several associations with high viral load, the clinical outcome of HSV-1-positive ICU patients did not differ significantly from the clinical outcome of HSV-negative patients. This finding indicates that HSV-1 viral loads in respiratory specimens are a symptom of a clinically poor condition rather than a cause of it. Longitudinal and therapy studies are therefore needed to distinguish between HSV-1 as a causative pathogen and HSV-1 as a bystander of pneumonia/ARDS.